Comparación de las técnicas quirúrgicas de orquiectomía tradicional y electrocirugía bipolar sobre la inflamación postquirúrgica en caninos - Bayas Punina, Joseph Mateo (2025)
Canine orchiectomy is a surgical procedure widely used in Veterinary Medicine due to the many benefits it brings to animal welfare, including the prevention of reproductive system diseases, population control, and improved behavior. In this study, conducted at the Veterinary Clinic of Bolívar State University, the postoperative effects of two surgical techniques were compared: traditional orchiectomy and orchiectomy using bipolar electrosurgery, with the aim of determining which technique generated a lower inflammatory response and promoted faster recovery. Forty male dogs of different breeds and ages were selected according to specific clinical criteria and randomly divided into two experimental groups of 20 animals each. They underwent clinical, hematological, and laboratory examinations for the anesthetic protocols and surgical intervention. Inflammation was assessed based on the quantification of C-reactive protein (CRP) in blood serum, taken 48 hours after surgery. Descriptive statistical analysis and Student's t-test were used with a significance level of 5%. The results showed significant differences between the two groups: group A (traditional technique) had higher CRP values, with a mean of 2,195 mg/l, while group B (bipolar electrosurgery) showed a mean of 1,465 mg/l, with a p-value of 0.0178 and a confidence interval of [0.134, 1.326], confirming that electrosurgery produced less inflammation. In addition, the average recovery time was 7.2 days for group A and 5.85 days for group B, showing a faster recovery with the bipolar electrosurgery technique. It was concluded that bipolar electrosurgery is an effective and advantageous alternative for orchiectomy in dogs, reducing post-surgical inflammation and optimizing recovery time, thus contributing to better clinical practice.